Implementation of the P5 Merdeka Curriculum in Developing Student Creativity in Modern Boarding School Institutions - Kamilatul Rohmah (Yayasan Literasi Altruis Khatulistiwa, 2025)
This research explores the implementation of the P5 Independent Curriculum in modern boarding schools to develop student creativity. The study aims to understand how the P5 program is applied and analyze activities that foster creativity. Using a narrative descriptive method, data is collected through interviews and observations. Findings reveal that the Independent Curriculum, which emphasizes the Pancasila Student Profile (P5) project, has been integrated into pesantren education through various extracurricular activities that support student creativity. However, several challenges hinder creativity development, including limited resources and rigid learning methods. To address these issues, proposed efforts include providing creativity training for teachers, adopting versatile and interactive teaching methods, enhancing facilities, increasing curriculum flexibility, and fostering a culture that values failure as part of learning. By implementing these solutions, student creativity can be nurtured in alignment with the goals of the Merdeka Curriculum in modern boarding schools